Denationalization in the Dominican Republic: Trapping Victims in the State's Administrative Maze. Issue 3 (15th September 2022) - Hunter, Wendy; Reece, Francesca
Abstract: The Dominican Republic retroactively stripped thousands of Dominico-Haitians of their Dominican citizenship yet managed to defuse international opprobrium over time. After a direct assault on people's citizenship status in 2013 provoked the human rights community's ire, the DR employed administrative obstructionism to maneuver around human rights activism and institutions. Policies instituted in 2014 appeared to offer a pathway for Dominico-Haitians to reinstate their citizenship yet were so administratively onerous that most of the affected population remains effectively stateless. Administrative obstructionism makes for an elusive target of attack because it unfolds across a series of decisions over time, transfers responsibility from a highly visible leader to dispersed and faceless bureaucrats, and is exceedingly difficult to monitor. Administrative obstructionism drags out proceedings, causing media attention to wither. Because international forces face special challenges in countering this strategy, a strong domestic opposition movement is necessary to sustain pressure on a rights-violating government.